Men at work - Kiarostami, Abbas 1940-2016 (Film Movement, 2006)
A comedy about four old friends who, driving back from a failed ski trip, encounter a strange and enormous rock by the side of the road above a lake. The men's frivolous attempt to dislodge the rock gradually disintegrates into a tale of betrayal, defeat and renewed hope
Orig.: Iran 2006